Effect of Different Irrigation Solutions on the Colour Stability of Three Calcium Silicate-Based Materials - Sobhnamayan F; Adl A; Ghanbaran S (Shiraz University of Medical Sciences, 2017)
Abstract: Statement of Problem: Previous studies have shown discoloration of mineral trioxide aggregate (MTA) in contact with root canal irrigation solutions. However, there are limited data on colour stability of other calcium silicate-based materials (CSMs). Objectives: This in vitro study aimed to evaluate the colour stability of three CSMs in contact with different irrigation solutions. Materials and Methods: Three CSMs including White MTA (wMTA) Angelus, calcium enriched mixture (CEM), and Biodentine were assessed in this study. Forty five samples of each material were mixed according to the manufactures' instructions and then placed in silicone tubes. After 24 hours, the materials were removed from the moulds and 9 samples of each material left dry or immersed in normal saline, 5% sodium hypochlorite (NaOCL), 2% chlorhexidinegluconate (CHX), or 17%EDTA for 24 hours. Colour changes were measured with a spectrophotometer. Data were evaluated with 2-way analysis of variance, one way analysis of variance and Tukey post hoc tests. Results: The highest discoloration of all materials was observed after contact with CHX. In the MTA Angelus and CEM cement groups, significant differences were observed between CHX and NaOCl and also between these two irrigants with the other three irrigants (p < 0.05). In the Biodentine group, CHX created statistically significant discoloration compared to other irrigants (p < 0.05). Only wMTA Angelus showed a significantly higher discoloration in contact with EDTA compared to normal saline and dry condition (p < 0.05). wMTA Angelus showed a significantly higher colour change compared with CEM cement and Biodentine after contact with NaOCl, CHX, and EDTA (p < 0.05). Conclusions: The contact of wMTA, CEM cement, and Biodentine with CHX should be avoided because this leads to severe discoloration. Contact with sodium hypochlorite also leads to discoloration of wMTA and CEM cements. Among of the three tested materials, wMTA showed the highest discoloration after contact with NaOCl, CHX, and EDTA.